Data structures using C : a practical approach for beginners - Jagtap, Amol M.; Mali, Ajit S. (Boca Raton : C&H/CRC Press, 2022)
'The data structure is a set of specially organized data elements and functions are defined to store, retrieve, remove and search for individual data elements. Data Structures: A Practical Approach for Beginners covers all issues related to the amount of storage needed, the amount of time required to process the data, data representation of the primary memory and operations carried out with such data. Data Structures using C: Practical Approach for Beginners book will help students learn data structure and algorithms in a focused. Resolves linear and non-linear data structures in C language using the algorithm, diagrammatically and its time and space complexity analysis. Covers interview questions and MCQs on all topics of campus readiness Identifies possible solutions to each problem. Includes real life and computational applications of linear and non-linear data structures This book is primarily aimed at undergraduates and graduates of computer science and information technology. Students of all engineering disciplines will also find this book useful'--
Includes bibliographical references and index.
Keywords: Data structures (Computer science).; C (Computer program language).